A description of eleven new species of Agaricus sections Xanthodermatei and Hondenses collected from Tibet and the surrounding areas - Zhou, Jun-Liang; Su, Sheng-Yu; Su, Hong-Yan; Wang, Bo; Callac, Philippe; Guinberteau, Jacques; Hyde, Kevin D; Zhao, Rui-Lin (Phytotaxa, 2016)
Specimens of Agaricus sections Xanthodermatei and Hondenses were collected in Tibet and the surrounding areas. All specimens were morphologically described and subjected to molecular phylogenetic analysis of the ITS and combined ITS, LSU and tef-1α sequence data using Bayesian and Maximum Likelihood methods. Twelve species were identified in this study, eleven of which were new species and one of which was identified in China for the first time. All of the identified species are described and illustrated with photo plates.